Communicative impairment and its neural correlates in Alzheimer's disease and frontotemporal dementia - Alexa Haeger; Janka Muising; Sandro Romanzetti; Bruno Fimm; Oliver Matz; Jörg B. Schulz; Stefan Heim; Kathrin Reetz (Brain and Behavior, 2024)
Abstract Objective Communication skills can deteriorate in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD); however, their clinical assessment and treatment in patient care can be challenging. In the present study, we aimed to quantify the distinctive communication resources and barriers reported by patients and their relatives in AD and FTD and associated these communicative characteristics with clinical parameters, such as the degree of cognitive impairment and atrophy in language‐associated brain areas. Methods We assessed self‐reported communication barriers and resources in 33 individuals with AD and FTD through an interview on daily‐life communication, using the Aachener KOMPASS questionnaire. We correlated reported communication barriers and resources with atrophy from high‐resolution 3T brain magnetic resonance imaging, neuropsychological assessment, and neurodegenerative markers from cerebrospinal fluid. Results Communicative impairment was higher in FTD compared to AD. Increased reported communication barriers in our whole sample were associated with the atrophy rate in the left middle temporal lobe, a critical site within the neuronal language network, and with depressive symptoms as well as the semantic word fluency from neuropsychological assessment. The best model for prediction of communicative impairment included the diagnosis (AD or FTD), semantic word fluency, and depressive symptoms. Conclusions Our study demonstrates that communication barriers and resources can be successfully assessed via a structured interview based on self‐report and report of patients’ relatives in practice and are reflected in neuroimaging specific for AD and FTD as well as in further clinical parameters specific for these neurodegenerative diseases. This can potentially open new treatment options for clinical practice and patient care.